2004
DOI: 10.1097/01.brs.0000105526.65485.92
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for the Presence of Neurogenic Lesions in Atypical Idiopathic Scoliosis

Abstract: The model derived in this study indicates that the probability of neurogenic lesions is extremely low in most patients with idiopathic scoliosis with atypical features. However, patients with severe curves despite skeletal immaturity and an abnormal neurologic examination have a significant probability of neurogenic lesions. Therefore, clinical efficiency will be enhanced by narrowing the indications for MRI to those patients with these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Scoliosis associated with chronic, disabling pain or pain that awakens the patient at night has been associated with tumors in the spine and spinal cord and warrants further investigation. Morcuende et al [35] reported 13 scoliosis patients who underwent MRI because of pain. None of them had an abnormal MRI, and none of their patients who had syringomyelia and Arnold-Chiari type I malformations complained of headache or neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis associated with chronic, disabling pain or pain that awakens the patient at night has been associated with tumors in the spine and spinal cord and warrants further investigation. Morcuende et al [35] reported 13 scoliosis patients who underwent MRI because of pain. None of them had an abnormal MRI, and none of their patients who had syringomyelia and Arnold-Chiari type I malformations complained of headache or neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…Others suggest that the clinical predictors of intraspinal lesions include sagittal plane malalignment of spinal contour [2,11,12], early-onset scoliosis [1,3,11,12], severe curves in immature individuals [14,15], double curves [11], pain [1,12] and male gender [16]. However, no specific indicator appears reliable or reproducible in its predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis with early age of onset, atypical shape (a single left thoracic or thoracolumbar curve), a rapidly progressive curve (>1º per month), a severe curve (>45º) despite immaturity, scoliosis with local pain, and male gender-all indicate a possible intraspinal pathology causing idiopathic scoliosis. 11,14,15 Patients with one or more of the above features should undergo MRI to rule out neural axis abnormalities, although in several studies there was no correlation between some of these features and intraspinal pathology.…”
Section: Discussionmentioning
confidence: 99%